Self-Regulation: A Step Towards Nursing Autonomy [Autorregulação: Um Avanço Em Direção À Autonomia Da Enfermagem] [la Autorregulación: Un Avance Hacia la Autonomía de Enfermería] - Pavez-Lizarraga, A (Universidad de Concepcion, 2019)
The nursing profession in Chile was affected by events that occurred in the Chilean society since the Constitution of 1980 and the modification of the Health Code in 1981, through the DL 3621 (Executive order). The construction of the definition of nursing introduced to the Chilean Health Code in the year 1997 provided legal support to the social function of the nurse, recognizing nursing as an autonomous profession. Objective: To analyze how the construction of the definition of nursing that was introduced in the Chilean Health Code, in its article No. 113, was developed. Method: Socio-historical approach, through the testimony of two nurses who were relevant actors in the construction of the definition of nursing. The interviews were analyzed through discourse analysis. Results: We present a critical reflection made by visionary nurses to construct a definition of nursing, which legally recognizes the profession in its social function, mainly in people’s health care. Conclusion: The historical event that legitimized the social function of the nurse meant a vindicating process to the social mission of the nurse’s work and became a sociopolitical milestone, however, more than twenty years later new challenges arise in the area of people’s health care, giving new value to self-regulation to strengthen autonomy and professional identity. © 2019, Universidad de Concepcion. All rights reserved.